Two new species of Caddisflies (Trichoptera: Insecta) from Lower-Hill Evergreen Forests of Southern Thailand - Suwannarat, Nannaphat; Malicky, Hans; Laudee, Pongsak (Zootaxa, 2018)
Two new species of caddisflies, Macrostemum nigralatum n. sp. and Anisocentropus tairomyenensis n. sp., are described and figured from lower-hill evergreen forests in southern Thailand. Wings of M. nigralatum are black, which distinguishes the new species from other related species. Anisocentropus tairomyenensis n. sp. is a member of the subgenus Anisomontropus and is characterized by the obvious basal expansion of the preanal appendages.